Cost of pediatric hospitalizations in Burkina Faso: A cross-sectional study of children aged <5 years enrolled through an acute gastroenteritis surveillance program. Issue 42 (29th September 2020) - Aliabadi, Negar; Bonkoungou, Isidore Juste O.; Pindyck, Talia; Nikièma, Moumouni; Leshem, Eyal; Seini, Emmanuel; Kam, Madibélé; Konaté, Souleymane; Ouattara, Ma; Ouédraogo, Boureima; Gue, Edmond; Nezien, Désiré; et al.
Abstract: Introduction: Diarrheal illness is a leading cause of hospitalizations among children <5 years. We estimated the costs of inpatient care for rotavirus and all-cause acute gastroenteritis (AGE) in two Burkina Faso hospitals. Methods: We conducted a cross-sectional study among children <5 years from December 2017 to June 2018 in one urban and one rural pediatric hospital. Costs were ascertained through caregiver interview and chart abstraction. Direct medical, non-medical, and indirect costs per child incurred are reported. Costs were stratified by rotavirus results. Results: 211 children <5 years were included. AGE hospitalizations cost 161USD (IQR 117–239); 180USD (IQR 121–242) at the urban and 154USD (IQR 116–235) at the rural site. Direct medical costs were higher in the urban compared to the rural site (140USD (IQR 102–182) vs. 90USD (IQR 71–108), respectively). Direct non-medical costs were higher at the rural versus urban site (15USD (IQR 10, 15) vs. 11USD (IQR 5–20), respectively). Indirect costs were higher at the rural versus urban site (35USD (IQR 8–91) vs. 0USD (IQR 0–26), respectively). Rotavirus hospitalizations incurred less direct medical costs as compared to non-rotavirus hospitalizations at the rural site (79USD (IQR 64–103) vs. 95USD (IQR 80–118)). No other differences by rotavirus testing status were observed. The total median cost of a hospitalization incurred by households was 24USD (IQR 12–49) compared to 75USD for government (IQR 59–97). Direct medical costs for households were higher in the urban site (median 49USD (IQR 31–81) versus rural (median 14USD (IQR 8–25)). Households in the lowest wealth quintiles at the urban site expended 149% of their monthly income on the child's hospitalization, compared to 96% at the rural site. Conclusions: AGE hospitalization costs differed between the urban and rural hospitals and were most burdensome to the lowest income households. Rotavirus positivity was not associated with greater household costs.